Modeling of pool fire and injury prediction considering different wind speeds and directions in offshore platform - Niazi, U.M. (Asian Research Publishing Network, 2016)
The offshore facilities are growing in number, size and complexity and so are the fire risks. Liquefied natural gas (LNG) is one of the most common hydrocarbon fuel produced in an offshore oil and gas platforms. LNG can cause different types of fires such as jet fire, pool fire, flash fire and fire ball. Among the various offshore accidents, pool fire is the most repeated phenomenon. It has the potential to cause significant injury to personnel, discontinuity of operations and damage to structure and equipment. Wind speed significantly affect the incident heat due to fuel radiation in case of pool fires in upwind and downwind direction. It is, therefore, requisite to quantify the hazards posed by pool fires in upwind and downwind direction at different wind speeds. The study is focused on modeling of pool fire using Computational Fluids Dynamics (CFD) with varying wind speed. For CFD modeling, Fire Dynamic Simulator (FDS) and Pyrosim are used. Effect of wind speed on smoke movement in downwind direction is investigated. The incident heat flux due to pool fire heat radiation is determined in upwind and downwind direction. Furthermore, radiative heat flux is utilized to calculate the impact on human for 1st degree of burn, 2nd degree of burn and death in upwind and downwind direction. The results exhibited that incident heat flux and probability of injury varies significantly in downwind direction by increasing wind speed and minor variation have been found in upwind direction. Â© 2006-2016 Asian Research Publishing Network (ARPN).